2024
DOI: 10.7554/elife.89306
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning to ordered membrane domains regulates the kinetics of secretory traffic

Ivan Castello-Serrano,
Frederick A Heberle,
Barbara Diaz-Rohrer
et al.

Abstract: The organelles of eukaryotic cells maintain distinct protein and lipid compositions required for their specific functions. The mechanisms by which many of these components are sorted to their specific locations remain unknown. While some motifs mediating subcellular protein localization have been identified, many membrane proteins and most membrane lipids lack known sorting determinants. A putative mechanism for sorting of membrane components is based on membrane domains known as lipid rafts, which are lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Altogether, these studies have led to the suggestion of the hydrophobic matching model, which proposes that gradients in bilayer thickness along the membranes of the secretory pathway contribute/drive the sorting and retention of TM proteins across the secretory pathway. Although there is compelling evidence for a TMD-based mechanism for targeting certain TM proteins to specific cell surface domains (Milovanovic et al, 2015), to localize type-II resident proteins of the cell surface and the Golgi membranes (Munro, 1995; Quiroga et al, 2013), and also to sort the type-III TM protein linker for activation of T-cells (LAT) by raft-mediated partitioning (Diaz-Rohrer et al, 2014; Lorent et al, 2017; Castello-Serrano et al, 2023), it remained unclear how this mechanism contributed to the retention, sorting and lateral segregation of Golgi resident enzymes and their substrates. Interestingly, by using a coarse-grained mathematical model of intra-Golgi transport, Dmitrieff et al showed that experimental data on the Golgi dynamics of secretory cargoes and Golgi residents cannot be explained if the hydrophobic matching mechanism is the sole retention mechanism for Golgi residents (Dmitrieff et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these studies have led to the suggestion of the hydrophobic matching model, which proposes that gradients in bilayer thickness along the membranes of the secretory pathway contribute/drive the sorting and retention of TM proteins across the secretory pathway. Although there is compelling evidence for a TMD-based mechanism for targeting certain TM proteins to specific cell surface domains (Milovanovic et al, 2015), to localize type-II resident proteins of the cell surface and the Golgi membranes (Munro, 1995; Quiroga et al, 2013), and also to sort the type-III TM protein linker for activation of T-cells (LAT) by raft-mediated partitioning (Diaz-Rohrer et al, 2014; Lorent et al, 2017; Castello-Serrano et al, 2023), it remained unclear how this mechanism contributed to the retention, sorting and lateral segregation of Golgi resident enzymes and their substrates. Interestingly, by using a coarse-grained mathematical model of intra-Golgi transport, Dmitrieff et al showed that experimental data on the Golgi dynamics of secretory cargoes and Golgi residents cannot be explained if the hydrophobic matching mechanism is the sole retention mechanism for Golgi residents (Dmitrieff et al, 2013).…”
Section: Discussionmentioning
confidence: 99%